(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides information on the research in the field of car exhaust gas catalysis, the history of development, the principle of operation of catalytic neutralizers, the composition of used catalytic active substances and the importance of this industry in the field of atmospheric air protection